2018
DOI: 10.1177/1545968318817823
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Spontaneous Motor Recovery Following Cortical and Subcortical Stroke in the Rat

Abstract: Background. Stroke is a leading cause of neurological disability, often resulting in long-term motor impairments due to damage to cortical or subcortical motor areas. Despite the high prevalence of subcortical strokes in the clinical population, preclinical research has primarily focused on investigating and treating cortical strokes. Moreover, while both humans and animals show spontaneous recovery following stroke, little is known about how injury location affects this process. Objective. To capture the hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…This combination of biomarkers more accurately predicted final outcome than initial impairment alone, including animals with profound impairments (Jeffers et al, 2018b). In a subsequent rodent study, the extent of poststroke impairment and recovery varied in relation to both cortical versus subcortical lesion location and the functional domain assessed (Karthikeyan et al, 2019), suggesting that lesion location may influence the level of recovery. In humans, both lesion location and volume have been shown to affect recovery (Chen et al, 2000), but volume, without consideration for location, is a relatively poor predictor of recovery (Chen et al, 2000;Page et al, 2013).…”
Section: Introductionmentioning
confidence: 87%
“…This combination of biomarkers more accurately predicted final outcome than initial impairment alone, including animals with profound impairments (Jeffers et al, 2018b). In a subsequent rodent study, the extent of poststroke impairment and recovery varied in relation to both cortical versus subcortical lesion location and the functional domain assessed (Karthikeyan et al, 2019), suggesting that lesion location may influence the level of recovery. In humans, both lesion location and volume have been shown to affect recovery (Chen et al, 2000), but volume, without consideration for location, is a relatively poor predictor of recovery (Chen et al, 2000;Page et al, 2013).…”
Section: Introductionmentioning
confidence: 87%
“…It is still to be answered if this is the case for skilled trained animals, and also for post-stroke reemergence and reorganization of motor maps. In a recent study, it was shown that striatal lesions are important for spontaneous recovery of non-skilled tasks (i.e., cylinder task) but not for dexterous reaching behavior (i.e., staircase task) (Karthikeyan et al, 2018). This is in accordance with the emerging consensus on the concept of cortical control over skilled motor behavior (Papale and Hooks, 2018).…”
Section: Two Phases Of Stroke Recovery – ‘Fast’ and ‘Slow’ Motor Relementioning
confidence: 99%
“…However, the tasks were untrained assessments of motor performance (eg, cylinder test, hanging wire test, pole test, and adhesive removal test), which typically show fewer deficits and more spontaneous recovery than skilled reaching tasks. 28 The animals in the study by Li et al 27 were also tested up to 8 weeks poststroke, and the majority of group differences were seen at this time point. According to these data, the Control mice in the present study should not demonstrate significant spontaneous recovery given that only 2 weeks of poststroke behavior were assessed.…”
Section: Discussionmentioning
confidence: 99%